Static output‐feedback control for interval type‐2 discrete‐time fuzzy systems. Issue 3 (25th October 2014) - Gao, Yabin; Li, Hongyi; Chadli, Mohammed; Lam, Hak‐Keung
Abstract : This article investigates the problem of reliable mixed H 2 / H ∞ control for discrete‐time interval type‐2 (IT2) fuzzy model‐based systems via static output‐feedback (SOF) control method. The number of fuzzy rules and the membership functions for the SOF controller are different from those for the plant. A sufficient criterion of reliable stability with mixed H 2 / H ∞ performance is derived for the closed‐loop system with sensor failure. The SOF controller is designed for two different cases (known sensor failure case and unknown sensor failure case) to guarantee the reliable stability with mixed H 2 / H ∞ performance. Moreover, novel criteria are presented to obtain the optical H 2 performance for the closed‐loop system. Finally, an example is used to verify the effectiveness of the proposed design scheme. © 2014 Wiley Periodicals, Inc. Complexity 21: 74–88, 2016